Inclusive Special Education and Science Teaching: teachers’ perception - Coelho, Caroline Pugliero (2025)
The study aims to investigate and describe teachers' perceptions of the challenges and possibilities of teaching science to students with disabilities. The study has exploratory, descriptive and qualitative characteristics, with subjects being 26 science teachers from the municipal network of a city on the Western Border of Rio Grande do Sul. For data collection, a questionnaire was used with questions related to the profile, training and perceptions about Inclusive Special Education and its implementation in science teaching. As for the results, it was evident that in the teachers' perception, continuing education is often promoted with themes decontextualized from the school reality, not considering the demands for inclusion. Furthermore, feelings of unpreparedness were reported, which create difficulties in planning and applying pedagogical proposals that meet the educational needs of students with disabilities.